2023
DOI: 10.12821/ijispm110103
|View full text |Cite
|
Sign up to set email alerts
|

Towards a framework for developing visual analytics in supply chain environments

Abstract: Visual Analytics (VA) has shown to be of significant importance for Supply Chain (SC) analytics. However, SC partners still have challenges incorporating it into their data-driven decision-making activities. A conceptual framework for the development and deployment of a VA system provides an abstract, platform-independent model for the whole process of VA, covering requirement specification, data collection and pre-processing, visualization recommendation, visualization specification and implementation, and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…When we started to research Visual Analytics (VA) systems for supply chain decisionmaking support [1], we found that supply chain actors have enormous and heterogeneous data and different domain analytics problems. Generally, to deploy VA, they need to deal with three aspects [2]: (1) Identifying decisions that VA can support known as VA tasks, (2) data requirements, and (3) VA system development. These aspects formulate the primary constructs of a VA system.…”
Section: Introductionmentioning
confidence: 99%
“…When we started to research Visual Analytics (VA) systems for supply chain decisionmaking support [1], we found that supply chain actors have enormous and heterogeneous data and different domain analytics problems. Generally, to deploy VA, they need to deal with three aspects [2]: (1) Identifying decisions that VA can support known as VA tasks, (2) data requirements, and (3) VA system development. These aspects formulate the primary constructs of a VA system.…”
Section: Introductionmentioning
confidence: 99%